2021
DOI: 10.1182/blood.2020008720
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of canonical WNT signaling ameliorates experimental sclerodermatous chronic graft-versus-host disease

Abstract: Chronic graft-versus-host disease (cGvHD) is a major life-threatening complication of allogeneic hematopoietic stem cell transplantation. The molecular mechanisms underlying cGvHD remain poorly understood and targeted therapies are not well established for clinical use. Here, we examined the role of the canonical WNT pathway in sclerodermatous cGvHD (sclGvHD). WNT signaling was activated in human sclGvHD with increased nuclear accumulation of the transcription factor β-catenin and WNT-biased gene expression si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…also demonstrated that the TME contains anti-tumor components ( 51 ). Although it is well known that the Wnt signaling pathway promotes tumor progression ( 52 , 53 ), Green et al. proved that Wnt3a derived from CAFs can both promote and inhibit the growth of breast tumors ( 54 ).…”
Section: Origin and Heterogeneity Of Cafsmentioning
confidence: 99%
“…also demonstrated that the TME contains anti-tumor components ( 51 ). Although it is well known that the Wnt signaling pathway promotes tumor progression ( 52 , 53 ), Green et al. proved that Wnt3a derived from CAFs can both promote and inhibit the growth of breast tumors ( 54 ).…”
Section: Origin and Heterogeneity Of Cafsmentioning
confidence: 99%
“…This PDF file includes: Materials and Methods Figs. S1 to S22 Tables S1 to S3 references (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) Other Supplementary Material for this manuscript includes the following: data files S1 and S2 arriVe checklist Mdar reproducibility checklist…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…In fibrosis, the canonical Wnt pathway is crucial for the stimulation of fibroblasts and the release of collagen. Wnt signaling accelerated the release of extracellular matrix components, promoted fibrosis, and triggered myofibroblast development from resting fibroblasts [ 107 ]. It should be noted that Wnt activation-induced fibrotic illness was more significant than the impacts of other fibrotic pathways.…”
Section: Role Of Wnt Pathway In Fibrosismentioning
confidence: 99%